Cover Picture: Combination of Solid‐Phase Micro‐Extraction and Direct Analysis in Real Time‐Fourier Transform Ion Cyclotron Resonance Mass Spectrometry for Sensitive and Rapid Analysis of 15 Phthalate Plasticizers in Beverages (Chin. J. Chem. 2/2015). Issue 2 (February 2015) - Wu, Mengxi; Wang, Haoyang; Dong, Guoqing; Musselman, Brian D.; Liu, Charles C.; Guo, Yinlong
<x xml:space="preserve">Abstract</x> The cover picture shows a new and expeditious approach for the identification and quantification of 15 phthalate plasticizers in beverages. Phthalates are legally regulated in foods and beverages in Europe, USA and China because of their potential healthy threaten. By a combined SPME and DART‐FTICR‐MS approach, phthalates at sub‐ng·mL−1 levels can be accurately analyzed in a short time, the limits of quantification (LOQs) were estimated to be at 0.3–5.0 ng·mL−1. This rapid and easy‐to‐use method provided a relatively high‐throughput and powerful analytical approach for quick testing and screening phthalates in beverages and water samples to ensure food safety. More details are discussed in the article by Guo et al. on page 213–219.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>